Friendship – the value of personal relationships in different periods of human of the life of human beings - Gulak, Ks. Stanisław (Nursing in the 21st Century, 2012)
FRIENDSHIP – THE VALUE OF PERSONAL RELATIONSHIPS IN DIFFERENT PERIODS OF HUMAN OF THE LIFE OF HUMAN BEINGS Contemporary man, busy with his career and consumption, often pushes friendship to the margin of life. In addition people whose consciousness is saturated with eroticism do not believe in the possibility of establishing deep, unselfish friendship, nor of the same sex or opposite sex. In such situation, we must now courageously defend human friendship and give it more attention and time. It can give our life better taste, because as the ancients used to say – “Friendship is the spice of life”. If we are attentive and open, we easily perceive how many signals inviting to establish friendship are sent by our neighbours. If they are to become the beginning of friendship they must be undertaken and developed. We can build friendship at every stage of our lives and in all human relations: peer, professional, neighbourhood, engagement, marriage and parenting. Although the erotic love usually develops among the persons more or less the same age, friendship makes no such limitations. The difference in age, education, gender, possession, religion does not constitute a great obstacle to friendship, if the friends find the common ground for meeting, exchanging ideas, dialogue and creative work. Frienshisp is the relationship, which accompanies man from childhood until death. Moreover – the real friendship exceeds the threshold of death. The word friendship is known to us from the early age, we often talked to our parents as small children, that in the kindergarten we had friends, not knowing the word. Today, as we are older people, we think we know who a friend is. We think that we are surrounded by our closest colleagues, but as the old but very wise proverb says: "You can get to know your true friends only in poverty". This is also true. For some people it is confidence, for others a way of solitude, for the next “something for the whole life. It is natural, that the friendship does not come from nowhere, a friend is not a person that will tell us: "from now on I am your friend". Friendship needs to be fostered from the very beginning, it should not be neglected, because like plants, which are not cultivated, it withers. The same situation is with us, when we lose contact with someone close to us, we suffer, after some time our confidence dies. Man loses his soul mate, becomes empty and useless. Friendship is a creation of a certain possibility to man. Without doubt it is also a gift, but what will we do with this gift? We are endowed with the free will and it depends on us what we do with it. Friendship is also a certain state in which you can persist. Everything starts with a friendship with oneself and has great problems with being friendly towards somebody. A good illustration of friendship is the conversation about taming between a fox and the Little Prince. Friendship is the ability to tame, that is to accept other human being. But in all this responsibility is a very important factor. We like to tame, that is why we willingly use the word "friend", but it is definitely worse with responsibility. Taming is done by itself, naturally. Responsibility is something that should be taken, because only in the melting-pot of events it turns out what we are like in friendship. In order to find friends one has to be patient, this is just what the fox tells the Little Prince. Friendship needs time. "To tame" means "to create links"… "If you tame me, we will need each other. You will be the only one for me in the world, And I will be the only one for you in the world’. A friend is the only one of his kind and cannot be replaced wit another one. Friendship is needed very much in our lives, but not everyone knows its value, day after day we try to spot among the crowd of people a person close to us and very much needed. Words are always imperfect, but friendship is the love realized, materialized in the relation of two people. So we can say, that there are so many definitions of friendship as the definitions of love, but in the whole we always talk about something essential, about something most important in man’s life.